Impact of Innovation & Certification To Sme Performance In F&B Sector - Rakhmatyar Ridha; Nila K. Hidayat (ADI Publisher, 2020)
The government has planned the programme “UKM Naik Kelas” to increase the number of halal certification but the objective was not achieved by the poor performance of SME. The study aimed to test the effects of innovation and Halal certification on SME performance. The innovation is measured by five dimensions are design and atmosphere, food and beverages, technology application, responsible business and human resources. The Halal certification is measured by two dimensions: knowledge on Halal concept and practices on Halalan Tayyiba. The SME performance is measured by three dimensions are profitability, business growth, and customer satisfaction. The study is carried out in the context of restaurants and café industry by distributing questionnaires to 200 owners of SMEs. The multiple linear regressions are used of this study to test both partially and simultaneously effects. The results show that either partially or simultaneously there are significant and positive effects of innovation and Halal certification on SME performance. The benefits of innovation can affect an organization’s business processes, product performance, and human resources performance which can optimally encourage SME performance. Meanwhile the Halal certification can grow the level of consumer trusts towards the brand and then encourage them to increase customer satisfaction and loyalty.